Presentation of the Contemporary Picture Book in Italy - Nives Zudić; Livio Sossi (University of Maribor Press, 2018)
The article presents the typical characteristics of picture books produced by Italian publishers, focusing mainly on the artistic and educational aspects of contemporary illustrations. The meeting of the child with the book, in early childhood, is entirely centered on reading the image. Illustrations in a book can suggest a specific story line, introducing their own language rules, which the child decodes. Therefore, the influence they exert on the child's early reading is certainly extraordinary. Hence, the authors begin their analysis by presenting the history of modern picture books in Italy, continue by examining the relationship between text and image, and try to illustrate the importance for the child to adequately understand the images. In addition, the article aims to highlight the importance of the early development of children's awareness of image reading and emphasises the importance of picture books for children's overall development